(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The aim of this research is to produce a multiplication wheel media product to increase the learning interest of fourth grade students at SD 06 East Pontianak. This research includes the development of Research and Development (R&D) with the ADDIE development model developed by Dick and Carry consisting of five steps, including (1) analysis, (2) design, (3) development, (4) implementation, (5) evaluation. The development of this learning media was validated by media experts and material experts. The validation results from all experts show that the development of this multiplication wheel learning media is very feasible, practical and effective for use in class IV elementary schools. This is proven by validation from media experts and material experts as well as student responses and effectiveness trials on students (measured by interest questionnaire questions). The average percentage of media experts is 92% in the "very feasible" category, the average percentage of material experts is 80% in the "decent" category. The average percentage result of the practicality questionnaire was 98% in the "very practical" category. The average results of the feasibility test before using the media were 49.58 low interest in learning, after using the media 95.83 high interest in learning. The final result of the average value of the interest questionnaire before and after being calculated using the N-gain formula was 0.93 according to the criteria for the success of the multiplication wheel media in the very effective category.